Pengaruh Variasi Metode Latihan Small-Sided Games terhadap Peningkatan Kapasitas Anaerobik Alaktasid pada Pemain Sepak Bola Usia Remaja (U-17) - Rahmansyah, Zamal; Imanudin, Iman; Hardwis, Syam; Fadli, Muhamad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study analyzes the effect of variations in Small-Sided Games (SSG) training methods on increasing anaerobic lactase capacity in U-17 soccer players by comparing the Pyramid and Interval methods. Using a quantitative pre-test and post-test experimental design, this study involved 20 players selected by purposive sampling, with anaerobic capacity measured through the Running-Based Anaerobic Sprint Test (RAST). The results of the Paired Sample T-Test showed that the Pyramid method significantly increased anaerobic lactase capacity, with a more significant decrease in Fatigue Index than the Interval method (p = 0.029, p < 0.05), indicating its effectiveness in maintaining explosive power and ATP-PCr regeneration. In contrast, the Interval method did not significantly increase (p = 0.598, p > 0.05). However, the Independent Sample T-Test results showed no significant difference between the two methods in increasing anaerobic capacity (p = 0.977). These findings suggest that both Pyramid and Interval methods can improve explosive power and ATP-PCr regeneration, with effectiveness that can be adjusted based on athlete needs and training strategies. In conclusion, the application of SSG as an effective and enjoyable training method, with further research involving larger samples, longer training durations, and additional analysis such as effect size to optimize training effectiveness. Keywords: Football, Small Sided Games, Pyramid Method, Interval Method, Anaerobic Alactasid